Analisis Peran Profesional Senior dalam Menumbuhkan Budaya Kerja Beretika Sebagai Upaya Kemajuan Perusahaan - Duwi Lestari; Marsyanada Marsyanada; Tries Ellia Sandari (Journal of Economic and Business Advancement, 2025)
This study discusses the role of senior professionals in fostering an ethical work culture as an effort to advance the company, given the challenges of modern organizations in maintaining productivity and reputation amid competition and stakeholder demands. Senior professionals not only make strategic decisions but also serve as ethical role models, mentors, and facilitators of the internalization of moral values in the work environment. This study uses a descriptive qualitative approach with literature review and document analysis methods to examine literature, journals, and documents related to professionalism, ethical culture, and leadership practices. The results show that senior professional strategies, such as value communication, mentoring, strengthening internal mechanisms, and reward and recognition systems, significantly increase the internalization of ethical values, employee engagement, compliance with the code of ethics, and work productivity. The impact of an ethical work culture led by seniors is also reflected in loyalty, job satisfaction, and company reputation. In conclusion, senior professionals are a key factor in creating an ethical work culture that supports sustainability, optimal performance, and organizational progress.